Not Just Another Cause of Dyspnea: Common Complaint Leads to a Rare Diagnosis. (8th April 2013) - Goyal, Hemant; Arora, Shitij; Duffoo, Frantz; Bhat, Utpal; Bhandari, Rekha; Rajupet, Sritha; Lwin, Kyaw Kyaw; Patel, Jigar
Abstract : A 62-year-old man with past medical history of type 2 diabetes mellitus (DM-2) and hypertension presented with progressive shortness of breath since three months. He was diagnosed with diabetic polyradiculopathy with diaphragmatic involvement and was started on intravenous immunoglobulin (IVIg) therapy. Rapid improvement was seen as evidenced by increased vital capacity and other pulmonary function parameters. Considering the patient's positive response to intravenous immunoglobulins (IVIg), this case strengthens the fact that diaphragmatic involvement in Type 2 Diabetes Mellitus can be a part of focal or polyneuropathy and that the pathogenesis is immune mediated.